Uniqueness of ductal carcinoma in situ of the breast concurrent with papilloma: implications from a detailed topographical and histopathological study of 50 cases treated by mastectomy and wide local excision. Issue 3 (8th July 2013) - Moritani, Suzuko; Ichihara, Shu; Hasegawa, Masaki; Endo, Tokiko; Oiwa, Mikinao; Shiraiwa, Misaki; Morita, Takako; Sato, Yasuyuki; Hayashi, Takako; Kato, Aya; Iwakoshi, Akari; Sato, Tomoko
<x xml:space="preserve">Abstract</x> Aims To clarify the diagnostic clues of ductal carcinomas in situ (DCIS) associated with papilloma and optimal clinical management of papilloma diagnosed on core needle biopsy (CNB). Methods and results A total of 50 surgically resected cases were examined histopathologically and topographically. Thirty‐nine cases (78%) spread in segmental fashion. Papilloma and DCIS were intermingled closely in 44 cases (88%), occupying the same areas in varying proportions from DCIS‐predominant to papilloma‐predominant. The two components occupied discrete areas and collided focally in six cases (12%). Most were non‐high‐grade. Cribriform and solid architectures with fibrovascular stroma were frequent. The cribriform pattern was unique, consisting of fused tubules separated by fibrovascular stroma. Intraductal myoepithelial cells were present to varying degrees in 40 cases (80%). In 38 cases (76%), points were identified where papilloma and DCIS coexisted or collided within a single lumen (CC point). Forty‐eight cases (96%) had either intraductal myoepithelial cells or CC points, implying that DCIS and papilloma existed in the same duct system. Radiology showed segmental abnormalities in 83% of the available cases. Conclusions Intraductal myoepithelial cells do not always guarantee benignity. Surgical resection is recommended for papilloma in CNB when radiology shows segmental abnormalities.